GDLN Seminar on Strengthening Disaster Risk Management in East Asia and the Pacific : Volume 4. Housing and Community Reconstruction after Natural Disasters - World Bank (Washington, DC, 2013)
In the GLDN seminar, the recovery procedures in the aftermath of the Kobe earthquake and the Asian tsunami were discussed. This introduction to Catastrophe Risk Financing Frameworks seminar provided participants with an understanding of catastrophe risk financing frameworks. In addition, it informed participants of new product lines in risk mitigation and risk finance and transfer and shared experiences of Bank-financed projects, including Turkey's Catastrophic Insurance Pool.